A Persistent Avian Formation on a South-Facing Slope, along the Northwest Rim of the Argyre Basin of Mars - Saunders, William; Haas, George; Miller, James (Journal of Scientific Exploration, 2022)
This is an examination of an avian-shaped feature that rests below a network of cellular structures found on a mound within the Argyre Basin of Mars. The area examined is located near 48.0° south and 55.1° west. A set of four supportive images provided by the Mars Global Surveyor and Mars Reconnaissance Orbiter spacecraft show the feature is persistent over a period of more than 20 years. The images reveal defining aspects of this avian feature, including a head, beak, body, eye, legs, feet, toes, wing, and feathers. When taken together, these components induce the visual impression of an avian-shaped formation that exhibits a unique set of proportional features. The claim of artificial construction is offered and the geoscientist author will examine natural mechanisms that could contribute to the creation of this feature and the testimony of three veterinarians will provide a critical analysis of the avian features. A terrestrial comparison of aesthetic and iconographic motifs is investigated. The request for further study and additional images of these structural components are also encouraged.